2016
DOI: 10.1038/srep31426
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, awareness, treatment, control of type 2 diabetes mellitus and risk factors in Chinese rural population: the RuralDiab study

Abstract: The study aimed to investigate prevalence, awareness, treatment and control of type 2 diabetes mellitus (T2DM), and to explore potential risk factors in rural areas of China. A total of 16413 individuals aged 18–74 years in rural districts were recruited from the Rural Diabetes, Obesity and Lifestyle (RuralDiab) study for the epidemiological research. Meanwhile, a meta-analysis including 7 published studies was conducted to validate the result of the cross-sectional study. The rates of crude and age-standardiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
72
4
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(90 citation statements)
references
References 29 publications
7
72
4
1
Order By: Relevance
“…A number of studies have shown that age is an important risk factor for diabetes [21]. However, the prevalence rate of diabetes in the current study had the peak in 50 to 59 age group, then a decreasing trend was observed, which is in conflict with the national study by Bragg et al [1].…”
Section: Discussioncontrasting
confidence: 94%
“…A number of studies have shown that age is an important risk factor for diabetes [21]. However, the prevalence rate of diabetes in the current study had the peak in 50 to 59 age group, then a decreasing trend was observed, which is in conflict with the national study by Bragg et al [1].…”
Section: Discussioncontrasting
confidence: 94%
“…Gender distribution of the participants reveals female predominance (59.66 %, 6th decade) which is consistent with Arslantas [8] and Liu [9] et al's studies (77.2%, 7th decade and 64.9%, 6th and 7th decade). These results may indicate the incidence of T2DM is higher than men around 6th decade which would be related with post-menopausal changes.…”
Section: Discussionsupporting
confidence: 89%
“…In the same year, Ho and Hwang et al demonstrated that diabetic kidney disease (DKD) was responsible for 46.2 and 43.2% of ESRD cases in Hong Kong and Taiwan, respectively [11,12]. The inadequate awareness and control of diabetes and hypertension has aggravated the health and socioeconomic burden of CKD and DKD in the Chinese population in several aspects, such as lower life expectancy, poor quality of daily life and the high cost of medical care [13][14][15][16]. Insufficient contracts with health services, delayed health-seeking behavior and frequent use of Chinese herbal medicines have also contributed to the high incidence and progression of CKD [17,18].…”
Section: Introductionmentioning
confidence: 99%